Karakterisasi Lahan Sawah Bukaan Baru Hasil Konversi Lahan Hutan di Desa Kalosi Kecamatan Towuti Kabupaten Luwu Timur - Irfandi Felix; Risma Neswati; Syamsul Arifin Lias (Jurnal Ecosolum, 2020)
The conversion of the function of productive agricultural land to non-agricultural land has taken place and is difficult to avoid as a result of the rapid rate of growth and development in an area so that agricultural production must be increased, especially food production to meet food needs with efforts to expand planting areas and the printing of new fields, but generally constrained by low-quality land. This study aims to determine the characteristics of the new openings paddy fields converted from forest land in the Village of Kalosi District Towuti for the development of irrigated paddy fields. This research method is descriptive, data collection is done by observations in the field and laboratory tests. The determination and sampling of soil in this study is purposive sampling. The results showed that the research location was suitable to be used as an irrigated field which had rainfall of ± 2329 - 3631 mm/year, an average temperature of 27oC, a minimum temperature of 23oC, a maximum temperature of 32oC, slope 0-8%, clay texture, dusty clay, sandy clay loam, H2O soil reaction 5.6 - 5.9, CEC 35 - 60 cmol/kg clay, C-organic > 2%, salinity 0.15 - 1.20 dS m-1, base saturation > 40%, base cation can be exchanged 11 – 19 cmol kg-1, the dominant type of mineral found kaolinite clay mineral and irrigation water quality has a pretty good standard of water quality.